2004
DOI: 10.1124/jpet.104.074484
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of Murine Collagen-Induced Arthritis by a Novel, Potent, Selective Small Molecule Inhibitor of IκB Kinase 2, TPCA-1 (2-[(Aminocarbonyl)amino]-5-(4-fluorophenyl)-3-thiophenecarboxamide), Occurs via Reduction of Proinflammatory Cytokines and Antigen-Induced T Cell Proliferation

Abstract: Demonstration that IB kinase 2 (IKK-2) plays a pivotal role in the nuclear factor-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
209
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 271 publications
(220 citation statements)
references
References 37 publications
10
209
0
1
Order By: Relevance
“…This is in concert with previous findings that TPCA-1 has higher inhibitory potency on either IKK-1 or IKK-2 than BMS-345541 Podolin et al, 2005). Both 10 μM BMS-345541 and 10 μM TPCA-1 exerted maximal inhibitory effects on the up-regulation of des-Arg 9 -bradykinin-and bradykinin -induced contraction, according to the inhibitory selectivity on IKK subtypes by BMS-345541 and TPCA-1, which suggests that both IKK-1 and IKK-2 subtype are involved in the transcriptional up-regulation of bradykinin B 1 and B 2 receptors.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This is in concert with previous findings that TPCA-1 has higher inhibitory potency on either IKK-1 or IKK-2 than BMS-345541 Podolin et al, 2005). Both 10 μM BMS-345541 and 10 μM TPCA-1 exerted maximal inhibitory effects on the up-regulation of des-Arg 9 -bradykinin-and bradykinin -induced contraction, according to the inhibitory selectivity on IKK subtypes by BMS-345541 and TPCA-1, which suggests that both IKK-1 and IKK-2 subtype are involved in the transcriptional up-regulation of bradykinin B 1 and B 2 receptors.…”
Section: Discussionsupporting
confidence: 91%
“…Data obtained previously have demonstrated that NF-κB signaling plays an important role in the process up-regulation of the bradykinin B 1 receptor (Moreau et al, 2007;Ni et al, 1998;Sabourin et al, 2002;Schanstra et al, 1998). Others have also shown that the NF-κB pathway is important for inflammatory cytokine enhanced expression of bradyinin B 1 and B 2 receptors in osteoblasts and fibroblasts (Brechter et al, 2008) ; TPCA-1 is a highly selective IκB kinase 2 inhibitor, the results from 57 assays gave a mean IC 50 = 17.9 nM on IKK-2 and has 22-fold selectivity over IKK-1 (Podolin et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…NF-B-DNA binding was significantly greater in human RA tissue compared with that from patients with osteoarthritis, and moreover, was localized to the sites of maximum tissue destruction (17). Increased NF-B-DNA binding activity has been demonstrated in synovial extracts from rats and mice following disease development (18,19). The inhibition of NF-B binding after IKK-2 inhibitor treatment has also been demonstrated in the mouse collagen-induced arthritis model (19) and the rat adjuvant-induced arthritis model (18).…”
Section: Discussionmentioning
confidence: 99%
“…Increased NF-B-DNA binding activity has been demonstrated in synovial extracts from rats and mice following disease development (18,19). The inhibition of NF-B binding after IKK-2 inhibitor treatment has also been demonstrated in the mouse collagen-induced arthritis model (19) and the rat adjuvant-induced arthritis model (18). In vivo imaging enabled us to visualize and quantify target activity in the inflamed joints of mice.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, with the same LPS stimulation, the translocation of NF-κB/p65 from the cytoplasm to nucleus was significantly blocked by pretreatment with 10 μmol/L lobolide (as shown in Figure 5A-3a, 3b, 3c) and 5 μmol/L 2-[(aminocarbonyl) amino]-5-(4-fluorophenyl)-3-thiophenecarboxamide (TPCA-1, Merck, USA) (as shown in Figure 5A-4a, 4b, 4c). TPCA-1 is an inhibitor of IKKα/β and selectively inhibits IKKβ 20-fold more than IKKα [18] . A final concentration of 0.1% (v/v) DMSO had no influence on LPS-stimulated NF-κB/p65 translocation to the nucleus, as reported previously (as shown in Figure 5A-5a, 5b, 5c) [19,20] .…”
Section: Lobolide Attenuated Nf-κb/p65 Nuclear Translocationmentioning
confidence: 99%